Risk spillovers and portfolio management between developed and African capital markets - Tunyiswa, Zipho Vuyolwethu (University of the Witwatersrand, Johannesburg, 2023)
This paper investigates spillover effects and portfolio diversification between two major developed stock markets (UK, US) and four emerging stock markets in Africa (South Africa, Nigeria, Egypt and Kenya). To this end, we apply the BK-spillover index model to daily spot indices during the period 2000–2021. The findings show that both the developed and the African markets have a sizeable and asymmetric long memory process. Based on the model's estimates, we also examine the hedging efficiency. The findings highlight the significance of overweighting developed country companies in ideal portfolios relative to stocks from African markets. Finally, we assess the practical implications for mixed developed-African stock portfolios, based on finding strong evidence of diversification benefits and downside risk reductions that confirm the usefulness of using developed market stocks in the African stock portfolio risk management
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Risk pullovers; Portfolio management; Emerging African markets; Capital markets; UCTD; SDG-8: Decent work and economic growth